Comparative Study Between Percutaneous Nephrolithotomy and Extra Corporeal Shock Wave Lithotripsy in Managing Renal Stones (Bangladesh Medical Journal, 2014)
To find out better treatment option in treating renal stone safely, expeditiously. A total of 90 patient were prospectively randomized for Percutaneous Nephrolithotomy (PCNL) (40) and Extra Corporeal Shock Wave Lithotripsy (ESWL) (50). Stone clearance, adjuvant procedures, hospital stay, post procedure morbidity, were compared for both methods. Stone clearance in PCNL and ESWL group was 87.50 and 66 percent respectively with a significant difference of clearance (P0.05). But in larger stones, stone clearance was 87.50% and 60.72% among PCNL and ESWL group respectively with significant difference in clearance between the groups (P